Activation of the Unfolded Protein Response and Proteostasis Disturbance in Parkinsonism-Dementia of Guam - Verheijen, Bert M; Lussier, Celina; Müller-Hübers, Cora; Garruto, Ralph M; Oyanagi, Kiyomitsu; Braun, Ralf J; van Leeuwen, Fred W (Journal of neuropathology and experimental neurology, 2020)
Abstract Guam parkinsonism-dementia (G-PD) is a progressive and fatal neurodegenerative disorder among the native inhabitants of the Mariana Islands that manifests clinically with parkinsonism as well as dementia. Neuropathologically, G-PD is characterized by abundant neurofibrillary tangles composed of hyperphosphorylated tau, marked deposition of transactive response DNA-binding protein 43 kDa (TDP-43), and neuronal loss. The mechanisms that underlie neurodegeneration in G-PD are poorly understood. Here, we report that the unfolded protein response (UPR) is activated in G-PD brains. Specifically, we show that the endoplasmic reticulum (ER) chaperone binding immunoglobulin protein/glucose-regulated protein 78 kDa and phosphorylated (activated) ER stress sensor protein kinase RNA-like ER kinase accumulate in G-PD brains. Furthermore, proteinaceous aggregates in G-PD brains are found to contain several proteins related to the ubiquitin-proteasome system (UPS) and the autophagy pathway, two major mechanisms for intracellular protein degradation. In particular, a mutant ubiquitin (UBB+1), whose presence is a marker for UPS dysfunction, is shown to accumulate in G-PD brains. We demonstrate that UBB+1 is a potent modifier of TDP-43 aggregation and cytotoxicity in vitro. Overall, these data suggest that UPR activation and intracellular proteolytic pathways are intimately connected with the accumulation of aggregated proteins in G-PD.